Translation and language validation of the Epworth sleepiness scale for children and adolescents (ESS-CHAD) into Brazilian Portuguese - Magda Lahorgue Nunes; Felipe Kalil; Marta Hemb; Camila dos Santos El Halal (Sleep Science, 2022)
Objective: This study aimed to translate the Epworth sleepiness scale for children and adolescents (ESS-CHAD) into Brazilian Portuguese. Material and Methods: The translation and language validation processes were carried out through translation, back translation, technical review, assessment of verbal comprehension/clarity of the scale by experts (four pediatric neurologists). After they have reached a final version of the ESS-HAD a sample of asymptomatic children and adolescents that were participants in another sleep project were invited to read and complete the questionnaire to evaluate comprehension by the aimed population. Results: Two independent researchers made the forward translation and it has around 90% of concordance. Minor disagreements were related to the position of adjectives in the sentence. No major difficulties were reported by the 3rd researcher that performed the back translation. After a consensus meeting with the four participants, we have reached a final version of the questionnaire. In the cognitive interviews, the scale was reportedly easy to understand to the 23 respondents. One adolescent suggested clarifying whether question 2 (likelihood of falling asleep watching TV or a video), referred to daytime or nighttime. The total ESS-CHAD score in this asymptomatic sample varied from 0-17, a mean score of 7.08±5.65. Discussion: The final version of the ESS-CHAD in Brazilian Portuguese was approved by the copyright owners and was well understandable by caregivers and adolescents. More studies are now necessary to use this questionnaire in a larger target population to verify its validity and internal consistency.